HUBUNGAN ILMU DAN AGAMA DITINJAU DARI PERSPEKTIF ISLAM - Hasir Budiman Ritonga (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
Now, religion, it seems, has begun to be removed from the life of the nation and state, and there is even a growing issue in the community that religion is going to be removed from formal education. Even though scientists strongly believe that knowledge if not accompanied by religion will be blind, as well as religion if without knowledge will undoubtedly be paralyzed. These two entry points show how important religion is to symbolize science as well as science is very much needed for religious practice. So in this paper the author tries to reveal in detail about the relationship between science and religion in the following discussion.